2019
DOI: 10.1002/jwmg.21656
|View full text |Cite
|
Sign up to set email alerts
|

Mayfield estimates versus apparent nest success in colonial geese

Abstract: Unbiased estimates of nest survival are often required to make robust inference about population and habitat management. We studied nest survival of lesser snow (Anser caerulescens caerulescens) and Ross's (A. rossii) geese at Karrak Lake, Nunavut, in Canada's central Arctic, 1995Arctic, -2012. We monitored nests throughout the nesting period, from early egg-laying to late incubation, and revisited nests after predicted hatch dates to determine nest fate. Despite high nesting density and high nest visibility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Increased emigration probability was linked to low nest success in both species (Wilson et al 2016), as been found in other colonial‐breeding birds such as Audouin's gulls Larus audouinii (Cam et al 2004) and lesser kestrels Falco naumanni (Serrano et al 2001). Ross's geese consistently had higher nest success (Traylor 2010, Kellett and Alisauskas 2019) and thus consistently lower emigration probability than snow geese (Wilson et al 2016). Such negative linkages of emigration probability to nesting success are consistent with adaptive behavioral response whereby individuals that have been unsuccessful in reproduction (or even skipped breeding and deferred an attempt to a subsequent year) disperse to habitats with improved chances of successful reproduction (Wilson et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Increased emigration probability was linked to low nest success in both species (Wilson et al 2016), as been found in other colonial‐breeding birds such as Audouin's gulls Larus audouinii (Cam et al 2004) and lesser kestrels Falco naumanni (Serrano et al 2001). Ross's geese consistently had higher nest success (Traylor 2010, Kellett and Alisauskas 2019) and thus consistently lower emigration probability than snow geese (Wilson et al 2016). Such negative linkages of emigration probability to nesting success are consistent with adaptive behavioral response whereby individuals that have been unsuccessful in reproduction (or even skipped breeding and deferred an attempt to a subsequent year) disperse to habitats with improved chances of successful reproduction (Wilson et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This effect size benchmarks well against the doubling of prey responses to the removal of invasive predators using traditional lethal techniques when they are effective (32). Protecting nests laid in the first third of the nesting season provides a disproportionately greater fitness value because their survival is naturally higher than for nests laid later (33)(34)(35).…”
Section: Discussionmentioning
confidence: 82%
“…Nests were revisited every 2 to 4 days to check their status, service the camera, and download video footage. Deploying cameras at nests was considered necessary to accurately determine nest fates and the identity of predators, and any effect of the cameras or observers at nests on the fate of nests was assumed to be constant across sites and years (33,44). Nest fates were determined either by direct observation of the hatch/failure event from the cameras (for the majority of nests) (see movie S1), by observing newly hatched chicks in the nest (for a minority of successful nests), or by eliminating the possibility of a hatch event by counting forward from known laying dates (for a minority of failed nests).…”
Section: Nest Monitoringmentioning
confidence: 99%
“…Researchers displacing females from nests can expose the nest to predators, which may bias estimates of DSP and nest survival if not mitigated or addressed in analyses (Rotella et al 2000). Reduced DSP following observer visits (Iles et al 2013, Rizzolo et al 2014, Meixell and Flint 2017) and nest-trapping events (Uher-Koch et al 2015) have been documented in some water bird studies, although other studies report no effects (e.g., Sedinger 1990, Kellett andAlisauskas 2019). We found evidence that visiting nests marginally decreased DSP and subsequently nest survival.…”
Section: Discussionmentioning
confidence: 99%